The Linkage between the Market of Stock Index Futures and Standard Spot: Evidence from China - LI, YOU (2020)
As a financial derivative which may hedge risk, stock index future had been sought after by many investors shortly after it was released. Whether the stock index futures stabilize or destabilize the spot market has been a heated topic in academia. Because of the unexpected stock market disaster in 2015, CFFCEX issued a series of restrictive policies on futures to stabilize the market. In the following four years, loosen rules were released to normalize the stock index transaction. Based on the background of policy adjustments, the author investigates the linkage between the two markets in China. Daily closing price data of three major stock indexes and corresponding stock index futures which were between April 2015 to December 2019 are utilized as the research object while GARCH family model and VAR model with tests are applied to examine the change of volatility in cash market and lead-lag price relationship. The results show that the volatility of stock market decrease after the strict rules and recovers to some extent during the relax period. This is because the recent information has greater power in stock price than old one and there is leverage effect in Chinese market. Besides, the price discovery function of futures is enhanced when the interaction between two markets becomes more frequent with the release of subsequent easing policies. The conclusion is helpful to fund managers, investors, and regulators with further possible policy implications.